The Impact of Covid-19 Pandemic on the Financial Performance of Go Public Companies During the PSBB and New Normal Phases - Devi, Sunitha; Musmini, Lucy Sri; Martin Mahardika, A.A.N. Yudha (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2023)
The decline in state tax revenue in 2020 can be attributed to the implementation of tax reductions aimed at stimulating economic growth. This measure primarily aims to provide support to the sectors of the economy that have experienced significant negative impacts due to the COVID-19 pandemic. The government expects that the economic difficulties resulting from the pandemic will result in a decrease in the financial performance of multiple businesses. The Slovin Formula is used for sample size determination. The data underwent analysis through the utilization of the Wilcoxon Signed Rank Test. The study findings suggest that the PSBB measures implemented during the COVID-19 pandemic resulted in higher average DER and receivable turnover, but lower average current ratio and ROA. No significant difference was found in the current ratio and debt-to-equity ratio (DER) among all industrial sectors. Significant variations were observed in the return on assets (ROA) and receivable turnover. No statistically significant variation was found in the current ratio, debt-to-equity ratio (DER), return on assets (ROA), and receivable turnover across all industrial sectors. The Consumer Goods Industry experienced improvements in the current ratio, return on assets (ROA), and receivable turnover, while witnessing a decline in the debt-to-equity ratio (DER). In contrast, the Property, Real Estate and Building Construction, Finance, Trade, Services, and Investment sectors observed a decline in both the current ratio and return on assets (ROA).